THE EFFECT OF ACCOUNTING KNOWLEDGE AND ORGANIZATIONAL EXPERIENCE ON ACADEMIC PERFORMANCE (STUDY ON ACCOUNTING STUDENTS) - Nanda, I Wayan Satya; Jurana, Jurana; Pattawe, Abdul; Sugianto, Sugianto (Accounting Studies and Tax Journal (COUNT), 2025)
This study aims to analyze the influence of accounting knowledge and organizational experience on academic performance. It uses a quantitative approach with data collected through questionnaires. The study population consists of 1,455 students with 314 respondents as the sample. Sampling was conducted using simple random sampling. Data analysis was conducted using multiple linear regression. The results of the study indicate that accounting knowledge and organizational experience have a positive influence on academic performance, both simultaneously and partially. Accounting knowledge reflects formal competence to improve academic performance, while organizational experience supports the development of soft skills, indirectly strengthening academic performance. This study enriches the literature on the influence of formal competencies (accounting knowledge) and informal competencies (organizational experience) simultaneously, which has not been extensively studied in the context of accounting students. These findings emphasize the importance of balancing academic and organizational activities to improve academic performance by formally recognizing students' active participation in organizational activities.